The interplay of social media exposure and language attitudes in shaping students' academic writing skills - Rini Damayanti; Roely Ardiansyah (BAHASTRA, 2026)
This study explores how social media exposure shapes students’ ambivalent language attitudes and influences their academic writing. In the digital era, students are continuously exposed to informal linguistic environments characterized by abbreviations, code-mixing, slang, and non-standard sentence structures. Using a qualitative descriptive-analytical design, this study involved 30 undergraduate students at a university in Surabaya, Indonesia. Data were collected through in-depth interviews, analysis of academic writing samples, and non-participant observations of students’ digital language practices. The findings identify ambivalent language attitudes as the study’s principal contribution. Students recognized the importance of standard Indonesian for academic writing while feeling more comfortable using informal digital language in everyday communication. This tension appeared in their writing through informal vocabulary, fragmented sentences, limited paragraph development, and weak cohesion. However, students with stronger metacognitive awareness, deliberate code-switching, systematic revision, and greater exposure to academic texts were better able to regulate their writing. These findings suggest that language attitudes constitute the key mechanism linking social media exposure and academic writing quality. Writing instruction should therefore promote register awareness and self-regulated writing strategies to help students navigate effectively between digital and academic language.